The Effect of Play Therapy on Improving Social Skills in ASD: A Systematic Review - Fara Pradika Putri; Choirun Nisa' Mufidatul Nabila (Jurnal Psikologi dan Konseling West Science, 2024)
Children with ASD show deficits in all social skills from infancy. Many therapy methods are being used and developed, including music therapy, physiotherapy, massage therapy, play therapy, etc. One that is currently being developed is play therapy. Play therapy can provide a positive stimulus for children. This writing is the result of a review of 12 in-depth journal articles about various types of play therapy interventions aimed at improving social abilities in children with autism spectrum disorders (ASD). Overall, this paper provides in-depth insight into how different types of play therapy interventions can significantly influence the social development of children with ASD.